Do romance ao filme: a metaficção como estratégia de constituição da forma nas narrativas Bufo & Spallanzani - Carvalho, Ana Cristina Teixeira de Brito (2013)
The purpose of this research is to discuss the literary and filmic narratives Bufo & Spallanzani based on the theoretical and methodological principles of narratology and intersemiotic translation; as such, it identifies and analyzes metafiction as a strategy of formal construction that gets established through aesthetic resources such as parody and the detective and crime genre. We initially offer a theoretical discussion of filmic adaptation, so as to articulate this process with the phenomenon of intersemiotic translation; next, we offer a theoretical investigation of metafictional resources, among which, parody, so as to argue for the different productions of meaning in the different sign systems. Since the research is supported on the dialogue between literature and cinema, the results reveal different principles of formal composition, as it refers to metafiction, thus corroborating the specificities inherent to each semiotic language.